2022
DOI: 10.3390/nu14040802
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Urinary and Blood Cadmium Levels in U.S. Adults with or without Comorbidities, 1999–2018

Abstract: Although cadmium (Cd) exposure has been declining in the United States (U.S.) over the years, the level of exposure for people with pre-existing comorbidities is unclear. This study characterized the trends of blood Cd levels (bCd) (n = 44,498) and urinary Cd levels (uCd) (n = 15,107) by pre-existing comorbidities among adults participating in the U.S. National Health and Nutrition Examination Survey. We calculated age- and sex-standardized annual geometric mean (GM) levels, and used aJoinpoint regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The primary measures of cadmium exposure include blood and urinary cadmium, with urinary cadmium primarily reflecting cadmium body burdens, whereas blood cadmium changes more rapidly during cadmium exposure ( 7 ). Although urinary cadmium is considered to be a good biomarker of long-term renal accumulation, it may be influenced by several factors related to renal cadmium accumulation, such as the proportion of cadmium transferred to the kidney, the subsequent half-life in the kidney, or methods used to compensate for changes in urinary dilution, such as creatinine excretion or urine density, all of which influence changes in urinary cadmium concentrations ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary measures of cadmium exposure include blood and urinary cadmium, with urinary cadmium primarily reflecting cadmium body burdens, whereas blood cadmium changes more rapidly during cadmium exposure ( 7 ). Although urinary cadmium is considered to be a good biomarker of long-term renal accumulation, it may be influenced by several factors related to renal cadmium accumulation, such as the proportion of cadmium transferred to the kidney, the subsequent half-life in the kidney, or methods used to compensate for changes in urinary dilution, such as creatinine excretion or urine density, all of which influence changes in urinary cadmium concentrations ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of diet and smoking on cadmium levels are significant, food leafy and root vegetables, cereals and offal are important sources of cadmium, long-term consumption of cereals and root vegetables will increase the accumulation of cadmium in the body ( 6 ). In addition, smoking is an important route of cadmium intake, the lungs have a higher cadmium absorption rate than the digestive tract, and cadmium levels in smokers are significantly higher than in non-smokers ( 7 ), and blood cadmium levels in non-smokers are less than 1 μg/L in most countries, whereas heavy smokers may have blood cadmium levels up to 7-fold higher. There are also differences in blood cadmium levels between different countries, with the average blood cadmium level of adults in the United States being lower than the average blood cadmium level of adults in Italy, Germany, Canada, and Australia ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although from 1999 to 2016, Americans experienced a dramatic decrease in Pb and Cd levels in their bodies, the ideal heavy metal content in the human body is 0 [22,23]. In available studies based on NHANES, the relationship of urinary and/or blood Pb and/or Cd with diabetes among the general population has been well established [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study of a young Taiwanese population, we showed that higher levels of urine lead and cadmium levels were correlated with a greater carotid intima-media thickness (CIMT), a biomarker of subclinical arteriosclerosis [ 6 ], and endothelium–platelet microparticles, which are associated with endothelial damage [ 7 ]. Being alert to such danger, human exposure to lead and cadmium has been decreasing for decades [ 8 , 9 ]. However, exposure to low doses of lead and cadmium are still associated with adverse health outcomes in recent epidemiological studies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%